Development of a microcomposite with single-walled carbon nanotubes and Nd2O3 for determination of paracetamol in pharmaceutical dosage by adsorptive voltammetry - Verónica Arancibia; Johisner Penagos-Llanos; Edgar Nagles; Olimpo García-Beltrán; John J. Hurtado (Elsevier, 2019)
This study presents for the first time a new composite of carbon paste (CP), single-walled carbon nanotubes (SWCNTs) and Nd2O3 (NdOX). This versatile composite (NdOX-SWCNT/CPE) was applied to the oxidation of paracetamol (PCM). The newly formed surface was characterized by scanning electron microscopy (SEM), electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The results showed greater conductivity and a higher surface area for the composite than those of the carbon paste alone. Moreover, the anodic peak currents for PCM increased from 1.6 to 3.6 µA with CPE and NdOX-SWCNT/CPE, indicating an increase of nearly 51.0% for the anodic peak current. On the other hand, the anodic peak potentials shifted from 0.67 to 0.57 V. The detection limits were 0.05 µmol/L with NdOX-SWCNT/CPE and 0.50 µmol/L with SWCNT/CPE. The relative standard deviations (RSDs) were 1.5% (n = 7). The accuracy and interference of the methods were evaluated with a urine chemistry control spiked with known quantities of PCM, uric acid, dopamine, ascorbic acid, caffeine, acetylsalicylic acid, tartrazine, sunset yellow, allure red, rutin, morin and metal ions. Finally, the novelty and usefulness of the composite were evaluated to quantify PCM in pharmaceutical dosage forms such as tablets, powders and syrups for children. Keywords: Paracetamol, Neodymium (III) Oxide, Single-walled carbon nanotubes, Pharmaceutical dosage